Antibacterial S. Aureus docking test from compounds contained from karamunting (rhodomyrtus tomentosa (aiton) hassk.) - Hadi, Samsul; Nastiti, Kunti (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2023)
Infection is a disease that causes high mortality in Indonesia, therefore it is necessary to search for antibacterial S. aureus compounds, one of which is the in silico method. The method in this study was docking using the PLANT software, the materials used were 10 compounds derived from karamunting and protein with the 3mzd code from RCSB, the results of the docking were then seen for interacting residues and types of bonds (hydrogen, electrostatic and hydrophobic) using discovery studio, besides that to predict activity using PASSonline and the data obtained is the value of Pa. The results of this study are docking scores -92.3386 to -66.8339 and Pa values of 0.242 to 0.598. The conclusion of this antibacterial research is that three compounds have the potential to be developed as antibacterials S. aureus, namely 5'-Desgalloylstachyurin, Rhodomyrtosone A and Rhodomyrtosone C.